Imajinasi Kreatif Dalam Kemampuan Berpikir Anak Sekolah Dasar, Penting Kah? - Mia Zultrianti; Nana Supriatna; Disman disman; Agus Gunawan; Santi Hendayani (Jurnal Elementaria Edukasia, 2023)
Creative thinking and critical thinking are one of the thinking skills that are often studied and developed to optimize thinking abilities. The initial basis of initial abilities is imagination. However, many people interpret the meaning of imagination as an unscientific fantasy. Using the literature review method, it was found that there is an ability that every human being has, including elementary school children, namely imagination. Creative imagination as a whole can be interpreted as an attempt to prove something about a person by taking several forms of existing goals, not only for the creator himself but also for other people. (RIBOT, 1906). We detail this effort to prove as a series of thought processes at the stages of having new ideas, flexibility, authenticity, expressing opinions, evaluating arguments, new ideas and making conclusions. This process combines critical thinking and creative thinking skills with rearranging indicators as needed. Humans cannot only use creative thinking skills or critical skills, everything goes hand in hand to create ideas and conclusions.